Quantitative Analysis and Correlation of HBeAg, HBeAb, and HBV DNA in Chronic Hepatitis B Patients in Swat, Khyber Pakhtunkhwa - Ali, Hamad; Rizwan, Muhammad; Ali, Qaisar; Ali, Arif; Ullah, Inam; Ahmad, Nadir (Futurity Medicine, 2025)
Aims: The research aims to determine quantitative values of HBeAg and HBeAb concentrations in chronic hepatitis B patients while assessing their relationship with serum hepatitis B DNA levels. Place and Duration of Study: This study was conducted at Saidu Teaching Hospital, Swat. This study lasts for 6 months, from December 2023 to April 2024. Methodology: This study comprised 100 patients with confirmed HBV DNA positive and a chronic hepatitis B. Exclusion criteria included those using antiviral medication, those with autoimmune or metabolic liver disorders, and those with co-infections (HCV, HIV, or HDV). HBeAg and HBeAb levels were assessed using CLIA, and HBV DNA was processed using qRT-PCR. Accuracy was ensured using internal quality control measures. To evaluate the correlations between HBV DNA, HBeAg, and HBeAb, data analysis was done using SPSS Version 17.0 and Pearson correlation. P-values less than 0.05 were regarded as statistically significant. Results: The mean viral load of the 100 patients was 60,800 IU/mL, and all of them tested positive for HBV DNA. HBeAb was 8.75 IU/mL on average, while HBeAg was 12.82 IU/mL on average. HBV DNA and HBeAg were found to be 59% associated, HBV DNA and HBeAb to be 46%, and HBeAg and HBeAb to be 77%, according to the correlation study. Epidemiological insights into the distribution and correlation of HBV markers in chronic hepatitis B patients are provided by these findings. Conclusion: This study concluded that not all chronic HBV patients have HBeAg and HBeAb levels, which are lower than those of HBV DNA. These findings offer valuable information on the serological trends of chronic hepatitis B, which might aid in comprehending how the illness develops.